Genetic diversity among geographically distant isolates of Neoparamoeba perurans - Hansen, Haakon; Botwright, Natasha A.; Cook, Mathew T.; Douglas, Alex; Downes, Jamie; Gallagher, Michael D.; Ruane, Neil M.; Matejusova, Iveta (Diseases of Aquatic Organisms, 2019)
The present study explored the use of 2 common genetic markers, the mitochondrial cytochrome oxidase I (COI) and the ribosomal internal transcribed spacer (ITS) to infer the relationship between geographically distant isolates of the protozoan gill parasite Neoparamoeba perurans, the agent responsible for amoebic gill disease in farmed Atlantic salmon worldwide. Present data confirmed that the ITS marker is suitable for Neoparamoeba species discrimination; however, it is not recommended as a population marker due to the presence of multiple copies of ITS within both N. perurans clonal and polycultures. On the other hand, in the partial COI gene analysed here, a low variability was observed, with 8 haplotypes recovered from N. perurans samples collected from Europe (Ireland, Norway, Scotland) and Tasmania (Australia). In Europe, the COI haplotypes which have more recently been detected in aquaculture are different to the haplotypes associated with the original gill disease emergence in Ireland in 1997 and Norway in 2006. The presence of unique COI haplotypes in different continents suggests the presence of multiple distinct reservoirs of the pathogen in both Europe and Tasmania. Isolates from additional geographical locations are required to fully understand the origins and routes for the spread of N. perurans worldwide.